Hyperventilation and cold-pressor stress echocardiography combined with automated functional imaging non-invasively detected vasospastic angina. (29th November 2010) - Suzuki, Kengo; Akashi, Yoshihiro J; Mizukoshi, Kei; Kou, Seisyou; Takai, Manabu; Izumo, Masaki; Shimozato, Takashi; Hayashi, Akio; Ohtaki, Eiji; Nobuoka, Sachihiko; Miyake, Fumihiko
Abstract : A 47-year-old male presented with chest discomfort while sleeping. The patient was suspected of having vasospastic angina (VSA) and underwent hyperventilation and cold-pressor stress echocardiography. No chest pain, ECG changes or decreased wall motion was found. However, automated function imaging (AFI) showed decreased peak systolic strain at the apex and postsystolic shortening at both the apex and inferior wall, which was not found before the test. The provocation test revealed 99% stenosis in the right coronary artery #2 at a dose of 50 μg acetylcholine and 90% stenosis in the left coronary artery #8 at a dose of 100 μg. The patient was thus diagnosed as having VSA. The present case demonstrates the usefulness of AFI combined with hyperventilation and cold-pressor stress echocardiography as a screening examination for VSA.